Axial sampling height outperforms site as predictor of wood trait variation - Dória, Larissa C.; Podadera, Diego S.; Lima, Rivete S.; Lens, Frederic; Marcati, Carmen R. [UNESP] (Brill Academic Publishers, 2019)
Covariation amongst wood traits along the stem axis is important to maintain hydraulic integrity ensuring sufficient sap flow to the canopy. Here, we test how wood traits (co)vary along the trunk and whether two seasonally dry Brazilian habitats (cerrado and caatinga) influence this variation in two co-occurring species, Tocoyena formosa (Rubiaceae) and Tabebuia aurea (Bignoniaceae). The samples were collected at five heights along the main trunk of three individuals per species in both sites. We used light, scanning and transmission electron microscopy to observe the wood traits. Out of 13 wood traits, nine show relationships with sampling height: eight traits predict height in T. formosa and five in T. aurea. Contrastingly, only three traits show differences between sites and only for T. formosa. The intratrunk wood variation is reflected by the hydraulically weighted vessel diameter showing a curvilinear relationship, disagreeing with the prediction of a continuous vessel widening from tip to base. In both species, the largest vessels are linked to the thinnest intervessel pit membranes. Wood density increases basipetally for both species, being site-dependent and correlated with vessel traits in T. formosa, and site-independent and determined by fiber wall thickness in T. aurea. Furthermore, the functional role of rays was found to be different for each species, and may be related to the marked difference in ray composition. In conclusion, both species show a unique adaptation to deal with height-related constraints using species-specific co-variation amongst wood traits, while site does not contribute much to the wood variation.
Keywords: Caatinga; cerrado; intraspecific variation; thickness of intervessel pit membrane